Analysis of the Grey Colour Intensity in Horses - Tóth, Zsuzsanna; Szőke, Szilvia; Bodó, Imre; Curik, Ino; Sölkner, Johann (Acta Agraria Debreceniensis, 2004)
An investigation of different grey coat colours and a connection between colour and age of horses was carried out with two Hungarian State Studs: Bábolna and Szilvásvárad. For objective measurement of coat colour Minolta Chromameter (Model CR-210) was used. The average value of L (lightness) level by Shagya and Pure Bred Arabian horses was 63.83 ± 2.23, for Lipizzan horses was x=71.00 ± 2.29 respectively. In each stud older horses (over 10 years of age) have a flea-bitten colour stage, which decreased the L value considerably. Changes in coat colour in connection with the greying process did not show an evident tendency in the three breeds.